Chondrogen™ injection for knee osteoarthritis using stem cells from Wharton’s Jelly - Badrul Akmal Hisham Md Yusoff,; Ahmad Farihan Mohd Don,; Norlelawati Mohamad,; Ramesh Saravanamuthu,; Karthik Chandran,; Raziana Rasib,; Premasangery Kathivaloo,; Lau, Felix Huey Yih (Penerbit Universiti Kebangsaan Malaysia, 2023)
Knee osteoarthritis constitutes a prominent source of pain and functional impairment, with its prevalence showing a consistent yearly increase. Current therapeutic strategies primarily revolve around addressing symptoms and, in severe cases, resorting to prosthetic joint replacement, yet they fail to target the underlying pathophysiological mechanisms driving degeneration. In this context, there is a growing interest in investigating mesenchymal stem cell (MSC) therapy as a potential remedy for osteoarthritis. Among the various MSC types under scrutiny, using Wharton’s Jelly-derived mesenchymal stem cells (WJ-MSCs) has garnered relatively scant attention. The present study represents a Phase I clinical trial of an open-label, single-arm design within this context. Its principal aim is to assess the safety and efficacy of administering mesenchymal stem cells derived from Wharton’s Jelly via intra-articular injection for patients diagnosed with knee osteoarthritis. Throughout six months, this investigation discerned a statistically significant overall improvement in clinical presentation relative to baseline. This improvement manifested as reduced analgesic consumption, diminished Visual Analog Scale (VAS) scores (19.5 to 18.7 mm, p = .00), and augmented functional assessment scores, including the IKDC Score (enhanced from 62.2 to 100, p = .00), KOOS Symptoms and Stiffness subscales (elevated from 76.8% to 10.6%, p = .00), as well as KOOS Pain subscale (upgraded from 74.4% to 10.1%, p = .00). The study encouragingly reported no significant adverse effects during the observation period. However, upon radiographic evaluation, no significant alterations were observed in terms of deformity angle (p = 0.957) or medial (p = 0.871) and lateral (p = 0.520) compartment joint space widths. To further elucidate the comparative efficacy of this treatment, it is prudent to contemplate a randomised controlled trial comparing it against the conventional hyaluronic acid regimen, thereby contributing to an enriched understanding of its therapeutic potential.